Phenotypic continuum of NFU1‐related disorders. Issue 12 (18th October 2022) - Kaiyrzhanov, Rauan; Zaki, Maha S.; Lau, Tracy; Sen, Sambuddha; Azizimalamiri, Reza; Zamani, Mina; Sayin, Gözde Yeşil; Hilander, Taru; Efthymiou, Stephanie; Chelban, Viorica; Brown, Ruth; Thompson, Kyle; et al.
Abstract: Bi‐allelic variants in Iron–Sulfur Cluster Scaffold ( NFU1 ) have previously been associated with multiple mitochondrial dysfunctions syndrome 1 (MMDS1) characterized by early‐onset rapidly fatal leukoencephalopathy. We report 19 affected individuals from 10 independent families with ultra‐rare bi‐allelic NFU1 missense variants associated with a spectrum of early‐onset pure to complex hereditary spastic paraplegia (HSP) phenotype with a longer survival (16/19) on one end and neurodevelopmental delay with severe hypotonia (3/19) on the other. Reversible or irreversible neurological decompensation after a febrile illness was common in the cohort, and there were invariable white matter abnormalities on neuroimaging. The study suggests that MMDS1 and HSP could be the two ends of the NFU1 ‐related phenotypic continuum.